1995
DOI: 10.1093/nar/23.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Mimosine, a novel inhibitor of DNA replication, binds to a 50 kDa protein in Chinese hamster cells

Abstract: We recently demonstrated that the plant amino acid, mimosine, is an extremely efficacious inhibitor of DNA replication in mammalian cells [P. A. Dijkwel and J. L. Hamlin (1992) Mol. Cell. Biol. 12, 3715-3722; P. J. Mosca et al. (1992) Mol. Cell. Biol. 12, 4375-4383]. Several of its properties further suggested that mimosine might target initiation at origins of replication, which would make it a unique and very useful inhibitor for studying the regulation of DNA synthesis. However, mimosine is known to chelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Furthermore, we demonstrated that the p50 mimosine binding activity is almost absent in a CHO cell line selected for resistance to 1 mM mimosine (ϳ10 times the lethal dose; 19,20). p50 partitions largely with the soluble cytoplasmic and nuclear fractions, and the ability to bind mimosine does not fluctuate demonstrably during the cell cycle (19).…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…Furthermore, we demonstrated that the p50 mimosine binding activity is almost absent in a CHO cell line selected for resistance to 1 mM mimosine (ϳ10 times the lethal dose; 19,20). p50 partitions largely with the soluble cytoplasmic and nuclear fractions, and the ability to bind mimosine does not fluctuate demonstrably during the cell cycle (19).…”
mentioning
confidence: 93%
“…We recently obtained evidence for a different (or additional) intracellular target. We showed that [ 3 H]mimosine can be specifically cross-linked to a 50-kDa polypeptide (p50) both in vivo and in vitro at concentrations equal to the minimum effective dose in vivo (19,20). Furthermore, we demonstrated that the p50 mimosine binding activity is almost absent in a CHO cell line selected for resistance to 1 mM mimosine (ϳ10 times the lethal dose; 19,20).…”
mentioning
confidence: 97%
See 3 more Smart Citations